Crowding-Out or Crowding-In: Government Health Investment and Household Consumption - Hao Cheng; Yu-Peng Zhi; Zi-Wei Deng; Qing Gao; Rui Jiang (Frontiers Media S.A., 2021)
This paper explores the relationship of government health investment and household consumption by applying a panel fixed effects model and Sobel-Goodman mediation tests to inland Chinese provinces. The empirical results highlight that government health investment has a crowding-in effect and can thus promote household consumption. Furthermore, the promotion effect on non-medical health consumption is greater than that on medical health consumption. The promotion effect of government health investment on rural household consumption is higher than that on urban household consumption, and the promotion effect on household consumption for northern provinces is higher than that in southern provinces. This heterogeneous effect is closely related to the difference between urban and rural development; and the economic levels of the northern and South regions. The mediation tests found that government health investment mainly promotes regional economic growth, and then increases household consumption. In the economic and social development process, the government should implement more effective medical and health care measures to increase social medical and health investment to improve the consumption level of households.